Amount of Brain Edema Correlates With Neurologic Recovery in Pediatric Cerebral Malaria. Issue 4 (April 2020) - Kampondeni, Samuel; Seydel, Karl B.; Zhang, Bo; Small, Dylan S.; Birbeck, Gretchen L.; Hammond, Collen A.; Chilingulo, Cowles; Taylor, Terrie E.; Potchen, Michael J.
Abstract : Background: Cerebral malaria (CM) remains a leading cause of mortality and morbidity in children in sub-Saharan Africa. Recent studies using brain magnetic resonance imaging have revealed increased brain volume as a major predictor of death. Similar morphometric predictors of morbidity at discharge are lacking. The aim of this study was to investigate the utility of serial cranial cisternal cerebrospinal fluid (CSF) volume measurements in predicting morbidity at discharge in pediatric CM survivors. Methods: In this case–control study, 54 Malawian pediatric CM survivors with neurologic sequelae evident at discharge who underwent serial magnetic resonance imaging scans while comatose were matched to concurrently admitted children with serial imaging who made full recoveries. Serial cranial cisternal CSF volume quantified by radiologists blinded to outcome was evaluated as a predictor of neurologic deficits at discharge. The probability of neurologic sequelae was determined using a model that included coma duration and changes in cisternal CSF volume over time. Results: Coma duration before admission was similar between cases and controls (16.1 vs. 15.3; P = 0.81), but overall coma was longer among children with sequelae (60 vs. 38 hours; P < 0.01). Lower initial CSF volumes and decreased volumes over time were both associated with a higher probability of neurologic sequelae at discharge. Conclusions: Among pediatric CM survivors with prolonged coma, lower initial CSF volume and decreasing volume during coma is associated with neurologic sequelae at discharge. These findings suggest that cerebral edema is an underlying contributor to both morbidity and mortality in pediatric CM. Abstract : Supplemental Digital Content is available in the text.